The Jurisprudential Status and Ranking of Imam Muhammad: A Research Analysis - Burhan Uddin; Dr. Zia Ur Rehman (Journal of Religion and Society, 2025)
Imam Muhammad ibn al-Hasan al-Shaybani occupies a distinguished and foundational position in the history of Islamic jurisprudence. As a principal student of Imam Abu Hanifa and a teacher of Imam al-Shafi‘i, he served as a crucial link between early Islamic legal scholarship and its later development. His contributions were not limited to transmitting the views of his teacher; rather, he expanded, refined, and systematized them through his own deep legal insight and analytical reasoning. His major works, including al-Mabsut, al-Jami‘ al-Kabir, al-Jami‘ al-Saghir, and al-Siyar al-Kabir, are considered masterpieces of Islamic legal literature and remain foundational texts in the Hanafi school of thought. Imam Muhammad’s jurisprudential approach blended rational analysis with strict adherence to scriptural sources, reflecting a balanced methodology that influenced not only Hanafi jurisprudence but the broader Islamic legal tradition. He played a vital role in documenting and codifying legal opinions, thereby preserving the legacy of the early jurists for future generations. His intellectual stature, clarity of expression, and methodical legal reasoning earned him respect across various schools of thought. Through his scholarly output and methodological rigor, Imam Muhammad helped shape the identity and resilience of Islamic law, securing his place as one of the most influential jurists in Islamic history. Keywords: Imam Muhammad Ibn Al-Hasan Al-Shaybani, Abu Hanifa, Jurisprudential, Islamic Legal, Islamic History,Al-Mabsut, Al-Jami‘ Al-Kabir, Al-Jami‘ Al-Saghir, And Al-Siyar Al-Kabir